Pengaruh Pengaturan Terhadap Posisi Status Kesehatan pada Anak dengan Pneumoia: Telaah Literatur - Agustina, Novita; Nurhaeni, Nani (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Children under five deaths caused by one of them by pneumonia every year in the world and Indonesia.Pneumonia causes respiratory problems that affect oxygen saturation. If not handled properly causes disabilityand death, then intervention is needed in the form of positioning that can improve children's health status.Objective: to identify research articles on positioning for an improvement in the health status of children withpneumonia. The method is literature review, which analyzes scientific articles from 3 databases: ScienceDirect, Whiley Online and Ebscohost. Keywords pneumonia, position *, and oxygenation. Criteria for inclusionof research articles, 2014-2019 and English. 9 journals obtained using the PICO formulation. Results:Semirecumbent, prone, fowler and lateral position adjustments can increase oxygen saturation, prevent VAPevents and stabilize hemodynamics. Conclusion: proper positioning is semirecumbent, prone, fowler, andlateral positions. Research is needed on the effectiveness of each position on the health status of children withpneumonia that is useful and can be implemented in nursing care in children with pneumonia in the hospital.